Penerapan Kontrak Lumpsum Anggaran Pemerintah pada Pekerjaan Jasa Konsultan dan Implikasinya pada Penyedia Jasa di Indonesia - Arry Budiyanto (Riviera Publishing, 2026)
This article discusses the dilemmas faced by Construction Consulting Service Providers when implementing lump sum contracts in projects funded by the government. The main issues arise during and after the consultancy services are performed. Lump sum contracts, which are based on payment for output, often lead to differing perceptions between Service Providers, Service Users, and Auditing Agencies regarding the accountability of payments. Service Providers sometimes feel disadvantaged, particularly when required to return payments for work performance that is not deemed satisfactory by Service Users or Auditors. This study analyzes the causes of these problems, focusing on the procurement process and the accountability of work completion. The research uses normative legal research, empirical legal research, and applies theoretical and legislative approaches, with primary and secondary data collected through reports and literature reviews. The findings suggest that the selection of lump sum contracts must align with the nature of the work, such as feasibility studies or surveys. Service Users should ensure standardized measurements to avoid discrepancies in perceptions among all parties involved. The study concludes that a shared understanding of the lump sum contract type is crucial for ensuring compliance with the contract's terms, and all parties must remain accountable, even if one feels disadvantaged by the other’s actions.